ACHWÉN MAWÉ Experiencia Gastronómica Multisensorial (2021)
Achwén Mawé, is a multisensory gastronomic experience that starts from the idea of ​​resignifying a historical dish, such as ajiaco, using the tools of industrial design to propose an experience that shows customs of our ancestral culture and make it known. In this way, the project begins by deconstructing the traditional Muisca ajiaco, taking into account its meanings, history and customs, for the creation of the experience. Framed in a non-linear, parallel execution methodology and without following any pre-existing model, it is made up of three main elements: Research, Exploration/Design and Verification. Built from the food design proposed in Francesca Zampollo's Food Design, the project designs the menu, the experience and the aspects around it in parallel. The proposal made, manages to transmit notions, customs and redefine ingredients, in addition to being a memorable experience for diners, thus proving its effectiveness and replicability.